2010
DOI: 10.1592/phco.30.11.1136
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin‐Resistant Enterococcal Urinary Tract Infections

Abstract: Enterococci are a common cause of urinary tract infections (UTIs) among hospitalized patients. The rising prevalence of vancomycin-resistant enterococci (VRE) is of particular concern within many institutions because of its association with increased mortality and health care costs, as well as limited treatment options. Clinicians need to differentiate between VRE-associated urinary colonization, asymptomatic bacteriuria, and UTIs in order to determine the need for treatment, optimal therapeutic options, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
63
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 71 publications
2
63
0
3
Order By: Relevance
“…A recent case series of fosfomycin outcomes in complex urinary tract infections due to multidrug-resistant organisms, including VRE, reported that urinary stents were associated with microbiologic failure in fosfomycin monotherapy (3). In order to effectively treat such infections, early hardware removal and complex antimicrobial therapy are often required (9). Based on our findings, combination therapy with fosfomycin and either daptomycin or amoxicillin is highly synergistic and results in enhanced bactericidal activity compared to fosfomycin alone against VRE.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…A recent case series of fosfomycin outcomes in complex urinary tract infections due to multidrug-resistant organisms, including VRE, reported that urinary stents were associated with microbiologic failure in fosfomycin monotherapy (3). In order to effectively treat such infections, early hardware removal and complex antimicrobial therapy are often required (9). Based on our findings, combination therapy with fosfomycin and either daptomycin or amoxicillin is highly synergistic and results in enhanced bactericidal activity compared to fosfomycin alone against VRE.…”
supporting
confidence: 55%
“…The antibacterial activity of fosfomycin increased from low to high concentrations but still remained bacteriostatic up to 16ϫ the MIC. Although fosfomycin concentrations are high at this exposure (1,024 to 2,048 g/ml), they represent concentrations comparable to those achieved in the urine of patients after a single 3-g oral dose (9). Interestingly, low exposures of fosfomycin (0.5ϫ the MIC) in combination with daptomycin, amoxicillin, or linezolid produced greater bacterial killing than high concentrations of fosfomycin alone (1 to 16ϫ the MIC) and bacterial killing similar to that induced by high fosfomycin exposures in combination with 0.5ϫ the MICs of secondary antibiotics.…”
mentioning
confidence: 65%
“…Patients with severe infections often have multisystem organ failure requiring renal replacement therapy, and continuous therapies are frequently preferred over intermittent hemodialysis in intensive care patients to avoid the development or exacerbation of hypotension and maximize fluid removal. Current dosing recommendations for piperacillin-tazobactam in patients receiving continuous renal replacement therapy (CRRT) (1,2) originate from either pharmacokinetic estimates or studies with relatively few patients and lower doses of CRRT than are used today (3,4). We designed this multicenter prospective observational study to evaluate the pharmacokinetics and pharmacodynamics of piperacillin-tazobactam in patients receiving CRRT with contemporary dialysis equipment and prescriptions.…”
Section: Introductionmentioning
confidence: 99%
“…This bacterium, is known by its natural resistance to some antibiotics; large (Arias and Murray, 2012;Heintz et al, 2010;Sartelli, 2010). The biogenesis and biofilm formation ability also contribute to the treatment of infections caused by E. faecalis.…”
Section: Introductionmentioning
confidence: 99%